Dionaea Honeypot Implementation and Malware Analysis in Cloud Environment - Shahrivartehrani, Shahrooz; Zainal Abidin, Shadil Akimi (Journal of Computing Technologies and Creative Content, 2016)
The purpose of this paper is analyzing malicious attacks in computer networks and the Internet. Dionaea honeypot is deployed on cloud environment to detect and collect malware attacks by reporting the malwares to external analysis service providers in order to understand the behaviour of malicious attacks, so malwares can be detected before becoming a serious threat in the information technology world.